Subcluster EK2 Annotation Report - McFerrin, Harris; Bollivar, David; Gurney, Susan; Adewumi, Olubusuyi; Edgington, Nicholas; Mayoral, Jaime; Rudner, Adam; Balish, Mitchell (QUBES, 2026)
This report describes features of actinobacteriophages assigned to subcluster EK2. Additional phages may have been added to the phagesDB database since the generation of this report.
Keywords: Annotation; Feature (linguistics); Genetic data; Genome; Human genome; dept.bio

Subcluster AZ1 Annotation Report - Beyer, Andrea; Bouklas, Tejas; Dojs, Madeline; Edgington, Nicholas; Harrison, Melinda; Rudner, Adam; Swerdlow, Sarah; Delesalle, Veronique; Page, Shallee (QUBES, 2025)
This report describes features of actinobacteriophages assigned to subcluster AZ1. Additional phages may have been added to the phagesDB database since the generation of this report.
Keywords: Annotation; DNA; Genome; Genomics; Human genome; Selection (genetic algorithm); dept.bio

Tissue-specific I-Smad mechanisms revealed by structure-function analysis in Drosophila - Simoncek, Ania; Sviridoff, Steven; Hays, J.; Graichen, Noah; Sulkowski, Mikolaj (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Inhibitory Smads (I-Smads) regulate TGF-β/BMP signaling through multiple distinct mechanisms, but whether different tissues preferentially employ specific mechanisms remains unknown. To address this question, we performed structure-function analyses of the Drosophila I-Smad Dad and its vertebrate orthologs Smad6 and Smad7 in neural and wing tissues, measuring in vivo outputs of BMP signaling. We identified a critical 24-amino acid putative DNA-binding domain (DNABD) within the MH1 domain of the Drosophila I-Smad, Dad, that is essential for inhibitory function in wing tissue but unessential in neural tissue. Structural analyses revealed that ΔDNABD disrupts a beta hairpin structure homologous to R-Smad DNA-binding regions. We also found that Dad requires an intact MH1 domain to disrupt wing development, whereas either MH1 or MH2 can independently disrupt BMP signaling in motor neurons. These findings support a model where Dad functions through MH1-mediated transcriptional regulation in wing primordium, but through multiple mechanisms in neurons. Comparative analysis revealed that vertebrate I-Smad orthologs also show tissue-specific activity patterns, with structural predictions suggesting that Smad6 retains ancestral DNA-binding capacity while Smad7 has evolved enhanced MH2-mediated functions. These results reveal context-dependent mechanisms of I-Smads that further the understanding of TGF-β/BMP pathway regulation.
Keywords: Biology; Cell biology; Context (archaeology); Decapentaplegic; Drosophila melanogaster; Function (biology); Gene; Genetics; Primordium; SMAD; Signal transduction; Vertebrate; dept.bio

Comparative genomic analysis of Cluster AZ Arthrobacter phages - Freise, Amanda; Furlong, Kieran; Klyczek, Karen; Beyer, Andréa; Chong, Rebecca; Edgington, Nicholas; Gibb, Bryan; Swerdlow, Sarah; Bendele, Madison; Cobb, Isobel; Mitchell, Zachary; Cresawn, Steven; et al. (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Bacteria in the Arthrobacter genus belong to the phylum Actinobacteria and are primarily soil-dwelling. Over 600 bacteriophages infecting Arthrobacter hosts have been isolated and sequenced, and genomic analyses show these phages to be highly diverse with mosaic genome architectures. We describe here a group of 32 Arthrobacter phages grouped in Cluster AZ, isolated on four different Arthrobacter strains all with siphoviral morphologies. The Cluster AZ phages exhibit a spectrum of diversity and can be subdivided into four subclusters. The diversity in minor tail protein and endolysin genes correlates partly with isolation host strain and may be predictive of the host range of these phages. Most of the Cluster AZ phages are temperate, form stable lysogens, and encode an integrase; however, an immunity repressor gene has not been identified. The intracluster diversity was analyzed in-depth at the whole genome level and through individual genes. As more Arthrobacter phages are isolated and analyzed they continue to provide new insights into phage evolution.
Keywords: Arthrobacter; Bacteria; Biology; Cluster (spacecraft); Computational biology; Computer science; Genetics; dept.bio

Alternative splicing and parallel patterns of gene expression underlie population and life history divergence in an amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikloaj; Brady, Steven (2025)
Keywords: Alternative splicing; Amphibian; Biology; Computational biology; Demography; Divergence (linguistics); Ecology; Evolutionary biology; Gene; Gene expression; Genetics; Life history; Messenger RNA; Population; RNA splicing; Sociology; dept.bio

Genomic comparison of the temperate coral Astrangia poculata with tropical corals yields insights into winter quiescence, innate immunity, and sexual reproduction - Stankiewicz, Kathryn; Guiglielmoni, Nadège; Kitchen, Sheila; Flot, Jean‐François; Barott, Katie; Davies, Sarah; Finnerty, John; Grace, Sean; Kaufman, Leslie; Putnam, Hollie; Rotjan, Randi; Sharp, Koty; et al. (G3 Genes Genomes Genetics, 2025)
Facultatively symbiotic corals provide important experimental models to explore the establishment, maintenance, and breakdown of the mutualism between corals and members of the algal family Symbiodiniaceae. Here, we report the de novo chromosome-scale genome assembly and annotation of the facultatively symbiotic, temperate coral Astrangia poculata. Though widespread segmental/tandem duplications of genomic regions were detected, we did not find strong evidence of a whole-genome duplication event. Comparison of the gene arrangement between As. poculata and the tropical coral Acropora millepora revealed considerable conserved colinearity despite ∼415 million years of divergence. Gene families related to sperm hyperactivation and innate immunity, including lectins, were found to contain more genes in Ac. millepora relative to As. poculata. Sperm hyperactivation in Ac. millepora is expected given the extreme requirements of gamete competition during mass spawning events in tropical corals, while lectins are important in the establishment of coral-algal symbiosis. By contrast, gene families involved in sleep promotion, feeding suppression, and circadian sleep/wake cycle processes were expanded in As. poculata. These expanded gene families may play a role in As. poculata's ability to enter a dormancy-like state (winter quiescence) to survive freezing temperatures at the northern edges of the species' range.
Keywords: Biology; Coral; Ecology; Evolutionary biology; Gene; Genetics; Genome; dept.bio

Isolated Abelisaurid Teeth from Gondwana and Dental Evolution in Abelisauridae - Hendrickx, Christophe; Núñez, Matías Soto; Araújo, Ricardo; Meso, Jorge G.; Maganuco, Simone; Ben-Salahuddin, Adé (Ameghiniana, 2025)
Abelisauridae were medium to large-bodied carnivorous dinosaurs with short, ornamented skulls, poorly recurved ziphodont teeth, and reduced forelimbs. They were the dominant terrestrial carnivores in many Gondwanan ecosystems during the Cretaceous. Their Jurassic origin, primarily based on the putative abelisaurid Eoabelisaurus from the Early Jurassic of Patagonia, remains debated, with many authors considering Abelisauridae as a strictly Cretaceous theropod radiation. Here, we describe several historically and stratigraphically important isolated theropod teeth from Gondwana, identified as belonging to abelisaurids using new cladistic and machine learning methods. Dental evolution in Abelisauridae was additionally explored using an updated version of a dentition-based data matrix focused on ceratosaurs. Results of this study show that the evolution of the dentition in abelisaurids was marked by a decrease in size of the mesialmost dentary teeth and the displacement of the tallest crowns towards the middle part of the maxilla. Two isolated abelisaurid teeth from the Late Cretaceous of India and Patagonia were also identified as the earliest published record of a non-avian theropod in Asia and an abelisaurid in Argentina, respectively. More importantly, isolated theropod teeth confidently referred to Abelisauridae from the Middle Jurassic of Madagascar provide additional support for the emergence of this clade in Gondwana before the Late Jurassic and reveal that the acquisition of abelisaurid dental traits occurred early in the evolutionary history of one of the most successful radiations of non-avian theropods from Europe and the Southern Hemisphere. © 2025 Asociación Paleontológica Argentina (APA)
Keywords: Biological evolution; Ceratosauria; Corona; Crown; Dentición; Dentition; Gondwana; Hemisferio Sur; Mandible (arthropod mouthpart); Phylogenetics; Southern Hemisphere; Terópodos; Theropoda; dept.bio

Tissue-specific I-Smad mechanisms revealed by structure–function analysis in Drosophila - Simoncek, Ania; Sviridoff, Steven; Hays, Joshua; Graichen, Noah; Sulkowski, Mikolaj (Life Science Alliance, 2026)
Inhibitory Smads (I-Smads) regulate TGF-β/BMP signaling through multiple distinct mechanisms, but whether different tissues preferentially employ specific mechanisms remains unknown. To address this question, we performed structure–function analyses of the Drosophila I-Smad, Dad, and its vertebrate orthologs Smad6 and Smad7 in neural and wing tissues, measuring outputs of BMP signaling in vivo. We identified a 24–amino acid putative DNA-binding domain within the MH1 domain of Dad that is essential for inhibitory function in wing tissue but unessential in neural tissue. Structural analyses revealed that ΔDNA-binding domain disrupts a β-hairpin structure homologous to R-Smad DNA-binding regions. We also found that Dad requires an intact MH1 domain to disrupt wing development, whereas either MH1 or MH2 can independently disrupt BMP signaling in motor neurons. These findings support a model where Dad functions through MH1-mediated transcriptional regulation in wing primordium, but through multiple mechanisms in neurons. Comparative analysis revealed that vertebrate I-Smad orthologs also show tissue-specific activity patterns, with structural predictions suggesting that Smad6 retains ancestral DNA-binding capacity, whereas Smad7 has evolved enhanced MH2-mediated functions. These results reveal context-dependent mechanisms of I-Smads that further the understanding of TGF-β/BMP pathway regulation.
Keywords: Domain (mathematical analysis); Function (biology); Homologous chromosome; Signal transduction; Vertebrate; Wing; dept.bio

Effects of intraspecies and interspecies competition on genetic device construction and performance - Thompson, Samantha; Williams, Adrian; Dill, Veronica; Marshall, Deven; Sawyer, Emily; Alexander, Mason; Rahn-Lee, Lilah; Shih, Joseph (mSphere, 2025)
ABSTRACT One exciting class of future genetic devices could be those deployed in microbes that join complex microbial environments in the wild. We sought to determine whether genetic parts designed for monoculture are predictable when used in co-culture by testing constitutive Anderson promoters driving the expression of chromoproteins from a plasmid. In Escherichia coli monoculture, a high copy number origin of replication causes stochastic expression regardless of promoter strength, and high constitutive Anderson promoter strength leads to selection for inactivating mutations, resulting in inconsistent chromoprotein expression. Medium- and low-strength constitutive Anderson promoters function more predictably in E. coli monoculture but experience an increase in inactivating mutations when grown in co-culture over many generations with Pseudomonas aeruginosa . Expression from regulated promoters instead of constitutive Anderson promoters can lead to stable expression in a complex wastewater culture. Overall, we show intraspecies selection for inactivating mutations due to a competitive growth advantage for E. coli that do not express the genetic device compared to their peers that retain the functional device. We show additional interspecies selection against the functional device when E. coli is co-cultured with another organism. Together, these two selection pressures create a significant barrier to genetic device function in microbial communities that we overcome by utilizing a regulated E. coli promoter. Future strategies for genetic device design in microorganisms that need to function in a complex microbial environment should focus on regulated promoters and/or strategies that give the microorganism carrying the device a selective or growth advantage. IMPORTANCE First-generation biotechnology focused on genetic devices designed for use in monoculture conditions. One class of next-generation biotechnology devices could be designed to function in complex ecosystems with other organisms, so we sought to create conditions where the genetic device retained function when the organism carrying it is in co-culture with other organisms. We discovered that when the genetic device is a significant resource burden on the organism carrying the device, mutations will be selected for due to intraspecies and interspecies selection pressures, and the device will be rendered non-functional. Therefore, genetic device design for complex ecosystems in next-generation biotechnology needs to balance functionality of the genetic device with the need to reduce resource burden on the organism carrying it.
Keywords: Competition (biology); Function (biology); Genetic diversity; Genetic screen; Model organism; Organism; Resource (disambiguation); Selection (genetic algorithm); chromoproteins; dept.bio; genetics; interspecies selective pressure; microbial communities; promoters

Alternative Splicing and Gene Expression Variation Underlie Population and Life History Differences in an Amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikolaj; Brady, Steven (Ecology and Evolution, 2025)
ABSTRACT Phenotypic variation is common across life history and among populations occupying different environments, yet the molecular mechanisms underlying these axes of divergence remain poorly understood. Much work has focused on gene expression as a link between genetic variation, environmental variation, and phenotypes, but post‐transcriptional processes such as alternative splicing—which affect how transcripts are assembled rather than how much of a transcript is produced—are increasingly recognized as additional modulators of plasticity and adaptation. Here, we examined gene expression and alternative splicing together in the wood frog ( Rana sylvatica ), an amphibian with a complex life cycle whose populations differ across replicated gradients of road adjacency and associated pollution. We found extensive transcriptomic differences between hatchlings and adults, with thousands of genes differentially expressed or spliced. Individuals clustered strongly by population for both expression and splicing. Differences at the habitat level were less extensive, but revealed two differentially expressed genes ( HSP70 and Gpsm2 ) and one differentially spliced gene ( Cd82 ) that consistently distinguished roadside and woodland populations. Overall, genetic differentiation between populations was low, suggesting that phenotypic and transcriptomic differences likely emerge in the presence of gene flow and reflect plastic responses. Together, these results highlight transcriptomic plasticity as an important mechanism shaping variation across both development and population differentiation.
Keywords: Alternative splicing; Amphibian; Gene; Gene expression; Genetic variation; Phenotypic plasticity; Population; Transcriptome; alternative splicing; dept.bio; gene expression; local adaptation; maladaptation; population divergence

Freshwater salinization leads to sluggish, bloated frogs and small, cramped embryos but adaptive countergradient variation in eggs - Brady, Steven; Kang, Samantha; Wang, Z.; Layne, Craig; Calsbeek, Ryan (Integrative and Comparative Biology, 2025)
Keywords: Amphibian; Aquatic ecosystem; Biology; Cottus; Ecology; Ecosystem; Freshwater ecosystem; Habitat; Population; Salinity; Soil salinity; dept.bio

Freshwater salinization of seasonal ponds: high salinity and stratification threaten critical, overlooked habitats - Brady, Steven; Benoit, Gaboury (Environmental Science & Technology, 2025)
Keywords: Biology; Critical habitat; Ecology; Environmental science; Fishery; Geology; Habitat; Oceanography; Salinity; Soil salinity; Stratification (seeds); dept,bio; peer-reviewed

The evolution of femoral morphology in giant non-avian theropod dinosaurs - Pintore, Romain; Hutchinson, John R.; Bishop, Peter J.; Tsai, Henry P.; Houssaye, Alexandra (Paleobiology, 2024)
Theropods are obligate bipedal dinosaurs that appeared 230 Ma and are still extant as birds. Their history is characterized by extreme variations in body mass, with gigantism evolving convergently between many lineages. However, no quantification of hindlimb functional morphology has shown whether these body mass increases led to similar specializations between distinct lineages. Here we studied femoral shape variation across 41 species of theropods (n = 68 specimens) using a high-density 3D geometric morphometric approach. We demonstrated that the heaviest theropods evolved wider epiphyses and a more distally located fourth trochanter, as previously demonstrated in early archosaurs, along with an upturned femoral head and a mediodistal crest that extended proximally along the shaft. Phylogenetically informed analyses highlighted that these traits evolved convergently within six major theropod lineages, regardless of their maximum body mass. Conversely, the most gracile femora were distinct from the rest of the dataset, which we interpret as a femoral specialization to “miniaturization” evolving close to Avialae (bird lineage). Our results support a gradual evolution of known “avian” features, such as the fusion between lesser and greater trochanters and a reduction of the epiphyseal offset, independent from body mass variations, which may relate to a more “avian” type of locomotion (more knee than hip driven). The distinction between body mass variations and a more “avian” locomotion is represented by a decoupling in the mediodistal crest morphology, whose biomechanical nature should be studied to better understand the importance of its functional role in gigantism, miniaturization, and higher parasagittal abilities.
Keywords: dept.bio; open-access; peer-reviewed

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Conner, L.M.; Goedert, D.; Fitzpatrick, S.W.; Fearnley, A.; Gallagher, E.L.; Peterman, J.D.; Forgione, M.E.; Kokosinska, S.; Hamilton, M.; Masala, L.A.; Merola, N.; Rico, H.; et al. (Chemosphere, 2024)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors associated with anthropogenic activities that affect many organisms across the planet – elevated salinity (e.g., from road de-icing salt) and temperature (e.g. from climate change). We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to pollution from road salt. When experimentally exposed to road salt, wood frogs showed reduced survival (especially those from ponds adjacent to roads), divergent developmental rates, and reduced longevity. Family-level effects mediated these outcomes, but high salinity generally eroded family-level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches. © 2024 Elsevier Ltd
Keywords: Amphibians; Climate change; Local adaptation; Maladaptation; Pollution; Road salt; dept.bio; peer-reviewed

Population Origin and Heritable Effects Mediate Road Salt Toxicity and Thermal Stress - Conner, Lauren M.; Goedert, Debora; Fitzpatrick, Sarah W.; Fearnley, Amber; Gallagher, Emma L.; Peterman, Jessica D.; Forgione, Mia E.; Kokosinska, Sophia; Hamilton, Malik; Masala, Lydia A.; Merola, Neil; Rico, Hennesy; et al. (2023)
Human impacts on wild populations are numerous and extensive, degrading habitats and causing population declines across taxa. Though these impacts are often studied individually, wild populations typically face suites of stressors acting concomitantly, compromising the fitness of individuals and populations in ways poorly understood and not easily predicted by the effects of any single stressor. Developing understanding of the effects of multiple stressors and their potential interactions remains a critical challenge in environmental biology. Here, we focus on assessing the impacts of two prominent stressors affecting many organisms across the planet – elevated salinity (an increasingly common pollutant in freshwater habitats) and elevated temperature. We examined a suite of physiological traits and components of fitness across populations of wood frogs originating from ponds that differ in their proximity to roads and thus their legacy of exposure to road salt pollution. When experimentally exposed to road salt, wood frogs showed reduced survival, especially those from ponds adjacent to roads, and delayed time to metamorphosis. Family level effects mediated these outcomes, but high salinity generally eroded family level variance. When combined, exposure to both temperature and salt resulted in very low survival, and this effect was strongest in roadside populations. Taken together, these results suggest that temperature is an important stressor capable of exacerbating impacts from a prominent contaminant confronting many freshwater organisms in salinized habitats. More broadly, it appears likely that toxicity might often be underestimated in the absence of multi-stressor approaches.
Keywords: Climate change; Maladaptation; SCSU-student; amphibians; dept.bio; local adaptation; pollution; road salt

Genomic comparison of the temperate coral Astrangia poculata with tropical corals yields insights into winter quiescence, innate immunity, and sexual reproduction - Stankiewicz, Kathryn H.; Guiglielmoni, Nadège; Kitchen, Sheila A.; Flot, Jean-François; Barott, Katie L.; Davies, Sarah W.; Finnerty, John R.; Grace, Sean P.; Kaufman, Leslie S.; Putnam, Hollie M.; Rotjan, Randi D.; Sharp, Koty H.; et al. (bioRxiv, 2023)
Facultatively symbiotic corals provide important experimental models to explore the establishment, maintenance, and breakdown of the mutualism between corals and members of the algal family Symbiodiniaceae. The temperate coral Astrangia poculata is one such model as it is not only facultatively symbiotic, but also occurs across a broad temperature and latitudinal gradient. Here, we report the de novo chromosome-scale assembly and annotation of the A. poculata genome. Though widespread segmental/tandem duplications of genomic regions were detected, we did not find strong evidence of a whole genome duplication (WGD) event. Comparison of the gene arrangement between A. poculata and the tropical coral Acropora millepora revealed 56.38% of the orthologous genes were conserved in syntenic blocks despite ∼415 million years of divergence. Gene families related to sperm hyperactivation and innate immunity, including lectins, were found to contain more genes in A. millepora relative to A. poculata. Sperm hyperactivation in A. millepora is expected given the extreme requirements of gamete competition during mass spawning events in tropical corals, while lectins are important in the establishment of coral-algal symbiosis. By contrast, gene families involved in sleep promotion, feeding suppression, and circadian sleep/wake cycle processes were expanded in A. poculata. These expanded gene families may play a role in A. poculata’s ability to enter a dormancy-like state (“winter quiescence”) to survive freezing temperatures at the northern edges of the species’ range.
Keywords: dept.bio

Kelp carbon sink potential decreases with warming due to accelerating decomposition - Filbee-Dexter, Karen; Feehan, Colette J.; Smale, Dan A.; Krumhansl, Kira A.; Augustine, Skye; Bettignies, Florian de; Burrows, Michael T.; Byrnes, Jarrett E. K.; Campbell, Jillian; Davoult, Dominique; Dunton, Kenneth H.; Franco, João N.; et al. (PLOS Biology, 2022)
Cycling of organic carbon in the ocean has the potential to mitigate or exacerbate global climate change, but major questions remain about the environmental controls on organic carbon flux in the coastal zone. Here, we used a field experiment distributed across 28° of latitude, and the entire range of 2 dominant kelp species in the northern hemisphere, to measure decomposition rates of kelp detritus on the seafloor in relation to local environmental factors. Detritus decomposition in both species were strongly related to ocean temperature and initial carbon content, with higher rates of biomass loss at lower latitudes with warmer temperatures. Our experiment showed slow overall decomposition and turnover of kelp detritus and modeling of coastal residence times at our study sites revealed that a significant portion of this production can remain intact long enough to reach deep marine sinks. The results suggest that decomposition of these kelp species could accelerate with ocean warming and that low-latitude kelp forests could experience the greatest increase in remineralization with a 9% to 42% reduced potential for transport to long-term ocean sinks under short-term (RCP4.5) and long-term (RCP8.5) warming scenarios. However, slow decomposition at high latitudes, where kelp abundance is predicted to expand, indicates potential for increasing kelp-carbon sinks in cooler (northern) regions. Our findings reveal an important latitudinal gradient in coastal ecosystem function that provides an improved capacity to predict the implications of ocean warming on carbon cycling. Broad-scale patterns in organic carbon decomposition revealed here can be used to identify hotspots of carbon sequestration potential and resolve relationships between carbon cycling processes and ocean climate at a global scale.
Keywords: Carbon sequestration; Decomposition; Deep sea; Forests; Latitude; Ocean temperature; Oceans; Seaweed; dept.bio; peer-reviewed

Plant growth promotion by rhizosphere dwelling microbes - Lewis Roberts, Elizabeth (Rhizosphere Engineering, 2022)
This work summarizes the roles of various plant promoting (PGP) microorganism on several types of plant hosts. In particular, rhizosphere dwelling bacteria and fungi that increase plant growth, protect plants from pathogens, and increase tolerance to abiotic stresses are presented. These traits are due, in part, to the production of enzymes, hormones, and a plethora a various metabolites produced by rhizosphere microorganisms that directly or indirectly benefit the plants. The impact of selective grazing by bacterivorous protozoa on plant growth promotion is also examined. In addition to reviewing research from other investigators, this paper introduces a recently isolated Pseudomonad bacterium that has demonstrated growth promotion and protection of heirloom tomato (Solanum lycopersicum) in the face of both abiotic and biotic stresses. Our findings indicate that the novel Pseudomonas koreensis strain could serve as an agricultural inoculant to induce plant growth and protection. The potential to create effective bioinoculum using rhizosphere microorganisms is discussed.
Keywords: Plant growth promoting Rhizobacteria; Plant growth promoting fungi; Protozoa; dept.bio

Salted roads lead to oedema and reduced locomotor function in amphibian populations - Brady, S.P.; Goedert, D.; Frymus, L.E.; Zamora-Camacho, F.J.; Smith, P.C.; Zeiss, C.J.; Comas, M.; Abbott, T.A.; Basu, S.P.; DeAndressi, J.C.; Forgione, M.E.; Maloney, M.J.; et al. (Freshwater Biology, 2022)
Human activities have caused massive losses of natural populations across the globe. Like many groups, amphibians have experienced substantial declines worldwide, driven by environmental changes such as habitat conversion, pollution, and disease emergence. Each of these drivers is often found in close association with the presence of roads. Here we report a novel consequence of roads affecting an amphibian native to much of North America, the wood frog (Rana sylvatica). Across 38 populations distributed from southern to central New England, we found that adult wood frogs living adjacent to roads had higher incidence and severity of oedema (indicated by obvious bloating caused by subcutaneous fluid accumulation) during the breeding season than frogs living away from the influence of roads. This effect was best explained by increased conductivity of breeding ponds, probably caused by runoff pollution from road salt used for de-icing. Oedema severity was negatively correlated with locomotor performance in more northerly populations. Interestingly, northern populations experience more intense winters, which tends to result in more de-icing salt runoff and increased energetic demands associated with overwintering cryoprotection needs. Thus, this emerging consequence of roads appears to impose potential fitness costs associated with locomotion, and these effects might be most impactful on populations living in regions where de-icing is most intense. Together, our findings reveal a novel set of impacts of roads and runoff pollution on wood frog physiology and performance, which seem likely to contribute to population decline. Given the global prevalence of roads and increasing salinisation of freshwater habitats, oedema and related impacts could be widespread consequences faced by amphibian populations across much of the planet's temperate zones. © 2022 John Wiley & Sons Ltd.
Keywords: amphibian; bloating; dept.bio; freshwater salinisation; peer-reviewed; performance; physiology; pollution; road salt runoff; winter de-icing

First records for spawning of caribbean acropora species in Colombian MPAs - Hudson, D.M.; Christie, B.L.; Gómez-Lemos, L.A.; Valcarcel, C.; Duque, D.; Arévalo, J.C.Z.; Rojas, J.; Reyes, O.; Marrugo, M.; Rosa, M.; Caicedo Torrado, I.A.; Tarazona, D.; et al. (Gulf and Caribbean Research, 2020)
Keywords: Acropora cervicornis; Acropora palmata; Coral restoration; Endangered coral; Sexual reproduction; dept.bio; peer-reviewed

Instructional models for course-based research experience (CRE) teaching - Hanauer, D.I.; Graham, M.J.; Arnold, R.J.; Ayuk, M.A.; Balish, M.F.; Beyer, A.R.; Butela, K.A.; Byrum, C.A.; Chia, C.P.; Chung, H.-M.; Clase, K.L.; Conant, S.; et al. (CBE life sciences education, 2022)
The course-based research experience (CRE) with its documented educational benefits is increasingly being implemented in science, technology, engineering, and mathematics education. This article reports on a study that was done over a period of 3 years to explicate the instructional processes involved in teaching an undergraduate CRE. One hundred and two instructors from the established and large multi-institutional SEA-PHAGES program were surveyed for their understanding of the aims and practices of CRE teaching. This was followed by large-scale feedback sessions with the cohort of instructors at the annual SEA Faculty Meeting and subsequently with a small focus group of expert CRE instructors. Using a qualitative content analysis approach, the survey data were analyzed for the aims of inquiry instruction and pedagogical practices used to achieve these goals. The results characterize CRE inquiry teaching as involving three instructional models: 1) being a scientist and generating data; 2) teaching procedural knowledge; and 3) fostering project ownership. Each of these models is explicated and visualized in terms of the specific pedagogical practices and their relationships. The models present a complex picture of the ways in which CRE instruction is conducted on a daily basis and can inform instructors and institutions new to CRE teaching.
Keywords: Educational; Engineering; Faculty; Humans; Mathematics; Models; Students; Teaching; dept.bio; educational model; engineering; human; mathematics; peer-reviewed; student; teaching; university

Seasonal variation in the bioaccumulation of potentially toxic metals in the tissues of Astrangia poculata in the northeastern United States - Trumbauer, W.; Grace, S.P.; Rodrigues, L.J. (Marine Pollution Bulletin, 2022)
Astrangia poculata inhabits coasts near dense human populations in the northeastern United States and may be exposed to elevated pollutants. No studies have assessed heavy metal concentration in temperate corals despite their proximity to anthropogenic activity. We collected colonies four times in one year and analyzed coral tissue for As, Cd, Cr, Pb, and Zn. Most heavy metals except for As were 1.5–3.3 times lower in summer compared to other seasons. Pb, As, and Cd were three orders of magnitude higher than concentrations for other Narragansett Bay benthic species, suggesting that A. poculata bioaccumulates more readily and/or inhabits more contaminated areas of the Bay. Zn, Pb, and As had similar concentrations to tropical corals inhabiting anthropogenically polluted sites. While physiological impacts are unknown, this population of A. poculata may have a higher tolerance for heavy metal pollution than most scleractinians, making it an interesting candidate for future studies. © 2021 Elsevier Ltd
Keywords: Animals; Anthozoa; Anthropogenic Effects; Article; Astrangia poculata; Astrangium poculatum; Bioaccumulation; Biochemistry; Chemical; Environmental Monitoring; Exposed to; Heavy; Heavy metal concentration; Heavy metals; Heavy metals pollution; Human population; Humans; Metals; Narragansett Bay; Narragansett bay; Pollution; Rhode Island; Seasonal variation; Seasonality; Seasons; Temperate; Tissue; Toxic metals; United States; Water Pollutants; animal; anthropogenic source; arsenic; benthos; bioaccumulation; cadmium; chromium; concentration (composition); concentration (parameter); coral; dept.bio; environmental monitoring; heavy metal; human; lead; metal derivative; nonhuman; peer-reviewed; pollution; season; seasonal variation; seasonality; toxic substance; water pollutant; zinc

Road salt compromises functional morphology of larval gills in populations of an amphibian. - Szeligowski, Richard V.; Scanley, Jules A.; Broadbridge, Christine C.; Brady, Steven P. (Environmental pollution (Barking, Essex : 1987), 2021)
Across the planet, winter de-icing practices have caused secondary salinization of freshwater habitats. Many amphibians are vulnerable because of permeable skin and reliance on small ponds, where salinity can be high. Early developmental stages of amphibians are especially sensitive to salt, and larvae developing in salt-polluted environments must osmoregulate through ion exchange in gills. Though ionoregulation in amphibian gills is generally understood, the role of gill morphology remains poorly described. Yet gill structure should affect ionoregulatory capacity, for instance in terms of available surface area. As larval amphibian gills also play critical roles in gas exchange and foraging, changes in gill morphology from salt pollution potentially affect not only osmoregulation, but also respiration and feeding. Here, we used an exposure experiment to quantify salinity effects on larval gill morphology in wood frogs (Rana sylvatica). We measured a suite of morphological traits on gill tufts—where ionoregulation and gas exchange occur—and on gill filters used in feeding. Larvae raised in elevated salinity developed larger gill tufts but with lower surface area to volume ratio. Epithelial cells on these tufts were less circular but occurred at higher densities. Gill filters showed increased spacing, likely reducing feeding efficiency. Many morphological gill traits responded quadratically, suggesting that salinity might induce plasticity in gills at intermediate concentrations until energetic demands exceed plasticity. Together, these changes likely diminish ionoregulatory and respiratory functionality of gill tufts, and compromise feeding functionality of gill filters. Thus, a singular change in aquatic environment from a widespread pollutant appears to generate a suite of consequences via changes in gill morphology. Critically, these changes in traits likely compound the severity of fitness impacts in populations dwelling in salinized environments, whereby ionoregulatory energetic demands should increase respiratory and foraging demands, but in individuals who possess structures poorly adapted for these functions. © 2021 Elsevier Ltd
Keywords: Amphibia; Animals; Article; Feeding; Freshwater habitats; Functional morphology; Gas exchange; Gill morphology; Gills; Humans; Ion exchange; Larva; Morphology; Osmoregulation; Osmosis; Osmotic stress; Plasticity; Pollution; Rana sylvatica; Ranidae; Road effect; Road salts; Roads and streets; Salinisation; Secondary salinization; Sodium Chloride; Surface area; amphibian; animal; animal cell; animal experiment; animal tissue; aquatic environment; breathing; cell density; cell structure; controlled study; dept.bio; developmental stage; embryo; energetic demand; energy; epithelium cell; exposure; foraging; functional morphology; gill; gill filter; gill length; gill tuft; human; larva; length; nonhuman; osmoregulation; peer-reviewed; plasticity; pollution exposure; road; salinity; salinization; salt; sodium chloride; surface area; volume

Physiological seasonality in the symbiont and host of the northern star coral, Astrangia poculata - Trumbauer, Wolfgang; Grace, Sean P.; Rodrigues, Lisa J. (Coral reefs (Online), 2021)
Assessing physiological responses that correspond to the normal range of seasonal variation can provide a better understanding of how environmental stressors may impact physiology. Most tropical corals exhibit seasonal variation in their host and symbiont physiology within a narrow range of environmental conditions. In temperate regions and at the northern end of its distribution, Astrangia poculata must adapt to wide ranges in seasonal variability. The species is facultatively symbiotic, and it is unclear if or how symbiotic state and, consequently, host physiology is affected by environmental seasonality. We collected colonies of A. poculata with a visible range of symbiotic states from Fort Wetherill State Park in Jamestown, RI in fall, winter, spring, and summer seasons of 2018–2019. We measured physiological parameters, including symbiotic state [chlorophyll (Chl) a and c2], total lipid content, and stable carbon (δ13C) and nitrogen (δ15N) isotopes of the host and symbiont. Seasonal variation occurred in all physiological parameters we studied. Specifically, Chl a, c2, and lipid content all reached low points in the spring, suggesting a lag, where the consequences of the coldest temperatures in the winter took up to three months to manifest in the tissue. There were seasonal fluctuations in host:symbiont ratios of δ13C, reflecting changing rates of autotrophy relative to heterotrophy during the year. While some autotrophy occurred during the year, isotopic evidence indicated that carbon acquisition in A. poculata was mostly heterotrophic in the winter. Based on δ15N, the symbiont was primarily responsible for nitrogen assimilation, although other sources likely contributed. Both carbon acquisition and nitrogen acquisition were more similar to that of other aposymbiotic coral species, regardless of the symbiotic state of A. poculata. Therefore, it may be more appropriate to view A. poculata as a unique aposymbiotic coral that is capable of symbiosis, rather than the reverse. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Anthozoa; Astrangia poculata; California; Jamestown; United States; autotrophy; chlorophyll a; dept.bio; heterotrophy; lipid; nitrogen; peer-reviewed; physiology; seasonal variation; seasonality; symbiont

Taste receptors in aquatic mammals: Potential role of solitary chemosensory cells in immune responses. - Barboza, Meghan Lee Bills; Reyno, Beau (Anatomical record (Hoboken, N.J. : 2007), 2021)
The sense of taste is associated with the evaluation of food and other environmental parameters such as salinity. In aquatic mammals, anatomic and behavioral evidence of the use of taste varies by species and genomic analysis of taste receptors indicates an overall reduction and, in some cases, complete loss of intact bitter and sweet taste receptors. However, the receptors used by taste buds in the oral cavity are found on cells in other areas of the body and play an important role in immune responses. In the respiratory tract, an example of such cells is solitary chemosensory cells (SCCs) which have bitter and sweet taste receptors. The bitter receptors detect chemicals given off by pathogens and initiate an innate immune response. Although many aquatic mammals may not have a role for taste in the assessment of food, they likely would benefit from the added protection that SCCs provide, especially considering respiratory diseases are a problem for many aquatic mammals. While evidence indicates that some species do not possess functional bitter receptors for taste, many do have intact bitter receptor genes and it is important for researchers to be aware of all roles for these receptors in homeostasis. Through a better understanding of the anatomy and physiology of aquatic mammal's respiratory systems, better treatment and management is possible. © 2021 American Association for Anatomy.
Keywords: Article; bitter taste; cell protection; chemoreceptor cell; dept.bio; homeostasis; innate immunity; mammal; nonhuman; peer-reviewed; receptor gene; respiratory system; respiratory tract disease; solitary chemosensory cell; sweetness; taste; taste bud

Homogenization and miniaturization of habitat structure in temperate marine forests. - Pessarrodona, Albert; Filbee-Dexter, Karen; Alcoverro, Teresa; Boada, Jordi; Feehan, Colette; Fredriksen, Stein; Grace, Sean; Nakamura, Yohei; Narvaez, Carla; Norderhaug, Kjell; Wernberg, Thomas (Global Change Biology, 2021)
Humans are rapidly transforming the structural configuration of the planet's ecosystems, but these changes and their ecological consequences remain poorly quantified in underwater habitats. Here, we show that the loss of forest-forming seaweeds and the rise of ground-covering 'turfs' across four continents consistently resulted in the miniaturization of underwater habitat structure, with seascapes converging towards flattened habitats with smaller habitable spaces. Globally, turf seascapes occupied a smaller architectural trait space and were structurally more similar across regions than marine forests, evidencing habitat homogenization. Surprisingly, such habitat convergence occurred despite turf seascapes consisting of vastly different species richness and with different taxa providing habitat architecture, as well as across disparate drivers of marine forest decline. Turf seascapes contained high sediment loads, with the miniaturization of habitat across 100s of km in mid-Western Australia resulting in reefs retaining an additional ~242 million tons of sediment (four orders of magnitude more than the sediments delivered fluvially annually). Together, this work demonstrates that the replacement of marine forests by turfs is a generalizable phenomenon that has profound consequences for the ecology of temperate reefs., (C) 2021 John Wiley & Sons, Ltd
Keywords: Australia; Ecosystem; Forests; Humans; Miniaturization; Seaweed; Western Australia; algal turf; climate change; dept.bio; ecological impact; ecosystem; epilithic algal matrix; forest; foundation species; habitat change; habitat structure; human; kelp forest; kelp forests; miniaturization; peer-reviewed; regime shift; seaweed; sediment pollution; species richness; temperate forest

Foliar Application of Copper Oxide Nanoparticles Suppresses Fusarium Wilt Development on Chrysanthemum. - Elmer, Wade H; Zuverza-Mena, Nubia; Triplett, Lindsay R; Roberts, Elizabeth L; Silady, Rebecca A; White, Jason C (Environmental science & technology, 2021)
Micronutrients applied as nanoparticles of metal oxides have shown efficacy in vegetable and other crops for improving yield and reducing Fusarium diseases, but their role in ornamental crop management has not been investigated. In 2017, 2018, and 2020, nanoparticles of CuO, Mn2O3, or ZnO were foliarly applied at 500 mug/mL (0.6 mg/plant) to chrysanthemum transplants and planted in potting soil noninfested or infested with Fusarium oxysporum f. sp. chrysanthemi. An untreated control and a commercial fungicide, Fludioxonil, was also included. Chrysanthemums treated with nanoscale CuO had a 55, 30, and 32% reduction in disease severity ratings compared to untreated plants in 2017, 2018, and 2020, respectively. Specifically, the average dry biomass for the three years was reduced 22% by disease, but treatment with nanoscale CuO led to a 23% increase when compared to controls. Similar trends with plant height were observed. Horticultural quality was improved 28% with nano CuO and was equal to the fungicide. Nanoscale Mn2O3 and the fungicide did not consistently reduce disease ratings or increase dry biomass each year. Nanoscale ZnO was ineffective. Nanoscale CuO-treated plants had 24 to 48% more Cu/g tissue than controls (P < 0.001). These findings agree with past reports on food crops where single applications of nanoscale CuO improved plant health, growth, and yield and could offer significant impacts for managing plant diseases on ornamentals.
Keywords: *Chrysanthemum; *Fusarium; *Metal Nanoparticles; *Nanoparticles; Article; Chrysanthemum; Copper; Copper oxide nanoparticles; Copper oxides; Crops; Disease ratings; Disease severity; Foliar application; Fungi; Fungicides; Fusarium; Fusarium oxysporum f. sp. chrysanthemi; Fusarium oxysporums; Fusarium wilt; II-VI semiconductors; Manganese oxide; Metal Nanoparticles; Metal nanoparticles; Nanoparticles; Nanoscale ZnO; Ornamental crops; Oxide minerals; Oxides; Soils; Untreated control; Zinc oxide; biomass; comparative study; controlled study; copper; copper oxide nanoparticle; crop protection; dept.bio; disease severity; elemental analysis; filamentous alga; foliage; food crop; gene; growing season; horticultural species; horticulture; hydrodynamics; metal nanoparticle; nanoparticle; nonhuman; oxide; peer-reviewed; plant disease; plant growth; plant height; plant tissue; trace element; wilt

A continuum of genetic mixing for conservation management along the (mal)adaptation spectrum: A comment on Hoffmann et al. - Crispo, Erika; Derry, Alison M.; Brady, Steven P. (Evolutionary Applications, 2021)
When restoring gene flow for conservation management, genetic variation should be viewed along a continuum of genetic divergence between donor and recipient populations. On the one hand, maintaining local adaptation (low divergence between donors and recipients) can enhance conservation success in the short term. On the other hand, reducing local adaptation in the short term by increasing genetic diversity (high divergence between some donors and recipients) might have better long-term success in the face of changing environmental conditions. Both Hoffman et al. (2020) and a paper we previously published in a Special Issue on Maladaptation in Applied Conservation (Derry et al., 2019) provide frameworks and syntheses for how best to apply conservation strategies in light of genetic variation and adaptation. A key difference between these two studies was that whereas Derry et al. (2019) performed a quantitative meta-analysis, Hoffman et al. (2020) relied on case studies and theoretical considerations, yielding slightly different conclusions. We here provide a summary of the two studies and contrast of the main similarities and differences between them, while highlighting terminology used to describe and explain main concepts. © 2021 The Authors. Evolutionary Applications published by John Wiley & Sons Ltd
Keywords: dept.bio; peer-reviewed

Gross and microscopic anatomy of the nasal cavity, including olfactory epithelium, of the florida manatee (Trichechus manatus latirostris) - Barboza, Meghan L. B.; Larkin, Iskande L.V. (Aquatic Mammals, 2020)
As a fully aquatic mammal, the Florida manatee (Trichechus manatus latirostris) spends a limited amount of time at the water's surface. However, as a mammal that breathes air, they do need to filter, warm, and humidify that air, and anecdotal evidence indicates manatees have a sense of smell. This study characterized the nasal turbinate system, including identification of the olfactory epithelium, and compared it to other mammals using a combination of gross and micro-anatomic examination. Major turbinates were present, including nasal, maxillary, and ethmoturbinates, but with minimal convolution. The respiratory epithelium was found throughout much of the nasal cavity and covered maxillary and nasal turbinates, as well as the septum. Mucus-producing cells and cavernous veins were extensive. The olfactory epithelium was found in the dorsocaudal ethmoturbinates. As a herbivore that feeds predominantly underwater, the manatee likely relies on taste and touch for assessing food and, therefore, does not need to use smell in the same way as other marine mammals such as mysticetes (Bouchard et al., 2019) and pinnipeds (Kowalewsky et al., 2006). However, there are still substantial numbers of olfactory cells, especially considering the decreased amount of exposure time to odorants when breathing at the surface. Therefore, the question remains of why manatees have maintained their ability to smell while other fully aquatic species such as odontocetes have not. Future research should focus on a combination of behavioral and molecular techniques to fully understand the olfactory capabilities of the Florida manatee. © 2020, European Association for Aquatic Mammals.
Keywords: Anatomy; Chemoreception; Mammalia; Manatee; Nasal; Olfaction; Pinnipedia; Trichechidae; Trichechus manatus; Trichechus manatus latirostris; anatomy; comparative study; dept.bio; herbivore; olfaction; peer-reviewed; sirenian

Detection of multiple grapevine viruses in New England vineyards - Borges, Darlan Ferreira; Preising, Stephanie; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington Luis (Crop Protection, 2020)
Vineyards in the New England region of the USA were surveyed for the occurrence of grapevine viruses. A total of ten vineyards were visited and 62 composite samples of leaves with the petioles were collected from symptomatic grapevines (Vitis spp.). All of the samples were assayed by double-antibody sandwich enzyme-linked immunosorbent assays (DAS-ELISA) using antibodies specific for four major grapevine leafroll-associated viruses (GLRaV-1, GLRaV-2, GLRaV-3, and GLRaV-4), grapevine fanleaf virus (GFLV), tobacco ringspot virus (TRSV), and tomato ringspot virus (ToRSV). Positive ELISA samples were further tested by reverse transcription polymerase chain reaction (RT-PCR) with primers specific for each of the viruses to confirm the ELISA results. Twenty-two samples were infected with at least one of the viruses tested. GLRaV-3 (24.19%) was the most prevalent virus detected followed by GLRaV-1 (12.90%), ToRSV (3.23%), and GLRaV-2 and TRSV (1.61%). This is the first study reporting on the presence of grapevine viruses in New England. Extensive surveys need to be conducted to evaluate the prevalence and economic impact of these viruses on New England vineyards. © 2020 Elsevier Ltd
Keywords: Grapevine fanleaf virus; Grapevine leafroll-associated virus 1; Grapevine leafroll-associated virus 3; Grapevine viruses; New England; Tobacco ringspot virus; Tomato ringspot virus; United States; Vineyards; Vitis; dept.bio; detection method; economic impact; pathogen; peer-reviewed; tobacco; vineyard; viral disease; virus

A fig deal: A global look at fig mosaic disease and its putative associates. - Preising, Stephanie; Borges, Darlan; de Queiroz Ambrósio, Márcia Michelle; da Silva, Washington L. (Plant disease, 2021)
Keywords: Badnavirus; Connecticut; Ficus; Phylogeny; Plant Diseases; dept.bio; peer-reviewed; phylogeny; plant disease

Body mass affects short‐term heterothermy in Neotropical bats - Czenze, Zenon J.; Dunbar, Miranda B. (Biotropica, 2020)
Recent work in Australia and Africa has shown that heterothermy is widespread among phylogenetically diverse tropical and subtropical mammalian taxa. However, data on the use of heterothermy by Neotropical mammals are relatively scant, and those studies that exist focus on insect-eating bats. We investigated the capacity of fruit-eating Neotropical bats to use heterothermy when exposed to acute cold temperatures, and compared this to previous data focused on insect-eating bats sampled from the same region and time of year. We measured rectal temperatures prior to acute cold exposure (1 hr at an air temperature of 6, 7, or 10°C), and again after exposure. Our data show considerable variation in the thermoregulatory patterns of Neotropical bats, and generally, our results show that smaller bats cool quicker and to a greater extent than larger bats. Our results highlight the importance of energy conservation even in environments in which resources are relatively abundant. © 2020 The Association for Tropical Biology and Conservation
Keywords: Africa; Australia; Chiroptera; Hexapoda; Mammalia; Neotropical Region; bat; body mass; dept.bio; diet; heterothermy; insect; neotropics; peer-reviewed; temperature effect; thermoregulation

Functional morphology of the taste buds of Florida manatee, Trichechus manatus latirostris - Barboza, Meghan L. B.; Larkin, Iskande L.V. (Marine Mammal Science, 2020)
The Florida manatee, Trichechus manatus latirostris, is a fully aquatic, threatened marine mammal for which increased understanding of their physiology, reproduction, and nutrition supports management decisions. Manatees may use taste to distinguish saltwater gradients, toxin detection, food assessment, and social interactions. This study sought to locate and characterize manatee taste buds comparing location, structure, number, and size to other species. Entire heads from manatees (6 males, 4 females) of various ages were obtained. The muzzle, tissue surrounding the nares, oral cavity, and epiglottis were examined grossly for pits and papillae. Tissues were examined using light and transmission electron microscopy. Within the predominant taste bud location, the tongue root, taste bud number was estimated using samples from four animals. The average number of taste buds within the tongue root was 11,534 (range 2,711–23,237) with sparse taste buds located on the soft palate and epiglottis. The location along the lateral surface of the tongue root and bordered by grooves, through which tastants could be easily transported, has functional significance. Large numbers of taste buds within the tongue root suggest that taste is an important component of manatee sensory systems and behavioral research would clarify this. © 2020 Society for Marine Mammalogy
Keywords: Animalia; Florida [United States]; Mammalia; Trichechidae; Trichechus manatus; Trichechus manatus latirostris; chemoreception; dept.bio; detection method; functional morphology; histology; manatee; marine mammal; peer-reviewed; sensory system; taste; taste bud; tongue

Marine heatwaves and the collapse of marginal North Atlantic kelp forests - Filbee-Dexter, K.; Wernberg, T.; Grace, S. P.; Thormar, J.; Fredriksen, S.; Narvaez, C. N.; Feehan, C. J.; Norderhaug, K. M. (Scientific Reports, 2020)
Extreme climatic events including marine heatwaves (MHWs) are becoming more frequent and severe in the Anthropocene. However, our understanding of how these events affect population dynamics of ecologically important species is limited, in part because extreme events are rare and difficult to predict. Here, we quantified the occurrence and severity of MHWs over 60 years in warm range edge kelp forests on both sides of the North Atlantic. The cumulative annual intensity of MHWs increased two- to four-fold during this period, coinciding with the disappearance of kelps. We experimentally demonstrated a relationship between strong and severe 2018 heatwaves and high kelp mortality in both regions. Patterns of kelp mortality were strongly linked to maximum temperature anomalies, which crossed lethal thresholds in both regions. Translocation and tagging experiments revealed similar kelp mortality rates on reefs dominated by healthy kelp forests and degraded sediment-laden algal ‘turfs’, indicating equal vulnerability to extreme events. These results suggest a mechanistic link between MHWs and broad-scale kelp loss, and highlight how warming can make ecosystem boundaries unstable, forcing shifts to undesirable ecosystem states under episodically extreme climatic conditions. © 2020, The Author(s).
Keywords: dept.bio

Impact of enriched environment during adolescence on adult social behavior, hippocampal synaptic density and dopamine D2 receptor expression in rats - Gabriel, Paul; Mastracchio, Toni-Ann; Bordner, Kelly; Jeffrey, Rachel (Physiology & Behavior, 2020)
Environmental enrichment (EE) is one experimental manipulation that induces changes in the brain. However, it is important to distinguish between physical and social components of enrichment. To this end we established four groups of rats reared in different enriched environments during the adolescent period. Our results indicate heightened social memory and increased spine density in dentate gyrus specifically in socially enriched animals. Physical enrichment increased spine density in CA1. Dopamine D2 receptor expression in hippocampus was decreased across all enrichment conditions. Altogether, our results demonstrate differing effects of physical and social enrichment, supporting an important role for environment in synaptogenesis, behavior, and dopaminergic signaling. © 2020 The Authors
Keywords: Adolescence; Animals; Article; Dopamine; Environment; Environmental enrichment; Hippocampus; Memory; Rats; Receptors, Dopamine D2; Social Behavior; Social enrichment; Synapse density; animal; animal behavior; animal experiment; controlled study; dentate gyrus; dept.bio; dept.psy; dopamine 2 receptor; dopaminergic transmission; environment; environmental enrichment; female; hippocampal CA1 region; hippocampus; male; memory; nonhuman; peer-reviewed; priority journal; protein expression; rat; social behavior; spine; synapse; synaptogenesis

Temperate urchins clear space for corals - Grace, Sean P; Feehan, Colette (Frontiers in Ecology and the Environment, 2020)
Keywords: Anthozoa; dept.bio; peer-reviewed

Genomic diversity of bacteriophages infecting Microbacterium spp. - Jacobs-Sera, Deborah; Abad, Lawrence A; Alvey, Richard M; Anders, Kirk R; Aull, Haley G; Bhalla, Suparna S; Blumer, Lawrence S; Bollivar, David W; Bonilla, J Alfred; Butela, Kristen A; Coomans, Roy J; Cresawn, Steven G; et al. (PloS one, 2020)
The bacteriophage population is vast, dynamic, old, and genetically diverse. The genomics of phages that infect bacterial hosts in the phylum Actinobacteria show them to not only be diverse but also pervasively mosaic, and replete with genes of unknown function. To further explore this broad group of bacteriophages, we describe here the isolation and genomic characterization of 116 phages that infect Microbacterium spp. Most of the phages are lytic, and can be grouped into twelve clusters according to their overall relatedness; seven of the phages are singletons with no close relatives. Genome sizes vary from 17.3 kbp to 97.7 kbp, and their G+C% content ranges from 51.4% to 71.4%, compared to ~67% for their Microbacterium hosts. The phages were isolated on five different Microbacterium species, but typically do not efficiently infect strains beyond the one on which they were isolated. These Microbacterium phages contain many novel features, including very large viral genes (13.5 kbp) and unusual fusions of structural proteins, including a fusion of VIP2 toxin and a MuF-like protein into a single gene. These phages and their genetic components such as integration systems, recombineering tools, and phage-mediated delivery systems, will be useful resources for advancing Microbacterium genetics.
Keywords: *Actinobacteria/vi [Virology]; *Bacteriophages/ge [Genetics]; *Genetic Variation; *Genome, Viral; Actinobacteria; Article; Bacteriophages; Bacteriophages/cl [Classification]; Bacteriophages/ip [Isolation & Purification]; Base Composition; DNA base composition; DNA, Viral; DNA, Viral/ge [Genetics]; Genes, Viral; Genetic Variation; Genome, Viral; Genomics; Microbacterium; MuF like protein; Phylogeny; VIP2 toxin; Viral Fusion Proteins; Viral Fusion Proteins/ge [Genetics]; bacterial genome; bacterial strain; bacterial toxin; bacteriophage; capsid protein; classification; comparative genomics; controlled study; dept.bio; fusion protein; gene sequence; genetic variability; genetic variation; genetics; genome size; genomics; isolation and purification; nonhuman; nucleotide sequence; peer-reviewed; phylogeny; unclassified drug; virology; virus DNA; virus fusion protein; virus gene; virus genome; virus infection; virus isolation